Pengaruh Tren Instagram #KaburAjaDulu terhadap Minat Wisatawan Domestik Berpergian ke Luar Negeri - Muhammad Solano; Isaghoji Isaghoji; Sri Utami; Rella Dwi Respati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of digital technology has significantly influenced tourist behavior, particularly through social media platforms such as Instagram. One of the emerging digital trends in Indonesia is the hashtag #KaburAjaDulu, which reflects digital escapism and encourages interest in traveling abroad. This study aims to analyze the influence of the Instagram trend #KaburAjaDulu on domestic tourists’ interest in traveling abroad. The research employed a quantitative descriptive method involving 96 respondents from Jakarta and Banten who actively use Instagram and have been exposed to content related to the hashtag. Data were collected through questionnaires, interviews, and observations, then analyzed using validity tests, reliability tests, classical assumption tests, simple linear regression, coefficient of determination, and hypothesis testing with SPSS version 30. The findings indicate that the Instagram trend #KaburAjaDulu has a positive and significant influence on domestic tourists’ interest in traveling abroad. Visual content, travel narratives, and viral digital trends on Instagram contribute to shaping perceptions and travel motivation among young people. This study contributes to the development of digital tourism studies, particularly regarding the role of social media trends in influencing tourist behavior in the digital era,